Morphological and genetic evidence support new species of Stenocercus (Iguania: Tropiduridae) from the Peruvian Andes - Castillo-Urbina, Ernesto; Rios-Roque, Shary; Barrera-Moscoso, Diego; Mendoza, Alejandro (Zootaxa, 2026)
The genus Stenocercus comprises a diverse group of 80 recognized species distributed across South America, with approximately 65% (52 species) occurring in Peru. The Department of Ancash, situated in the central Andes and encompassing the Cordillera Negra and Cordillera Blanca, is a topographically complex region marked by prominent geographic barriers that may promote allopatric speciation and influence patterns of Andean biodiversity, particularly within Stenocercus lineages. Populations previously assigned to S. chrysopygus from the puna habitats of Ancash exhibit notable variation in diagnostic traits and coloration, suggesting that this taxon may represent a species complex. However, inconsistent morphological diagnoses and limited genetic data have hindered accurate taxonomic resolution, underscoring the need for integrative approaches. Furthermore, a recent study showed that only populations from the Santa River Valley correspond to S. chrysopygus sensu stricto, while the other populations assigned to the distribution of S. chrysopygus constitute lineages of different species. In this study, we describe Stenocercus aguilari sp. nov. from Huari Province, Ancash Department, and present a phylogenetic hypothesis of its position based on the mitochondrial ND2 gene. We applied multivariate morphological analyses of scale counts using MANOVA and Gaussian Mixture Models, as well as molecular species delimitation approaches based on both distance-based and tree-based single-locus methods. All analyses support the taxonomic distinctiveness of S. aguilari sp. nov. Morphologically, the new species belongs to the group characterized by granular scales on the posterior surface of the thighs, vertebral scales similar in size and shape to adjacent rows, and three caudal whorls per autotomic segment. It is distinguished from other members of this group by the absence of a posthumeral mite pocket, the presence of a Type 1 postfemoral mite pocket, higher number of midbody scales and the presence of a distinct black patch on the pelvic region of the venter in adult males. Finally, the focal lineage is divergent from all nominal species in the Stenocercus genus for which respective data are available by >14.8% uncorrected pairwise distance in the ND2 gene.